(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Permatasari AAAP, Rosiana IW, Wiradana PA, Lestari MD, Widiastuti NK, Kurniawan SB, Widhiantara IG. 2022. Extraction and characterization of sodium alginate from three brown algae collected from Sanur Coastal Waters, Bali as biopolymer agent. Biodiversitas 23: 1655-1663. Sodium alginate extracted algae are gaining attention as alternative biopolymer materials. This research aimed to extract and characterize the natrium alginate from three brown algae obtained from Sanur Beach, Denpasar, Bali, Indonesia. Alginate extraction was carried out using acid hydrolysis by Na2CO3 with further purification using isopropyl alcohol. Physicochemical characterization was carried out using FT-IR. The results showed that Sargassum aquifolium and Turbinaria ornata had higher yields (%) than Padina australis (P<0.05). There was no significant difference (P>0.05) in water content, protein content, fat content and pH of the three brown algae. Overall, these three types of brown algae have values ??that are close to the sodium alginate standard set by the Food Chemical Codex (FCC), except for the results of Padina australis in the yield parameter. The functional group Na which is characteristic of sodium alginate is present in all alginate isomers, but there are some functional groups that are still not available in the extraction process in this study based on FT-IR analysis. These findings indicate that sodium alginate extracts from various types of brown algae have specific characteristics as defined by the Food Chemical Codex (FCC) and show great potential to be used as biopolymer materials, especially in the biomedical field.